2022
DOI: 10.1186/s41181-022-00183-y
|View full text |Cite
|
Sign up to set email alerts
|

A simple and automated method for 161Tb purification and ICP-MS analysis of 161Tb

Abstract: Background 161Tb is a radiolanthanide with the potential to replace 177Lu in targeted radionuclide therapy. 161Tb is produced via the neutron irradiation of [160Gd]Gd2O3 targets, and must be purified from 160Gd and the decay product 161Dy prior to use. Established purification methods require complex conditions or high-pressure ion chromatography (HPIC) which are inconvenient to introduce in a broad user community. This study aims to find a simpler small solid-phase extraction (SPE) column meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…161 Tb was produced via the neutron bombardment of enriched [ 160 Gd][Gd 2 O 3 (98.2%) targets using the high thermal neutron flux (3 × 10 14 neutrons/cm 2 /s) BR2 reactor at SCK-CEN (Belgium) [ 26 ] and subsequently purified at TRIUMF using a semi-automated TRASIS system with solid phase extraction (SPE) resins (TK211, TK 212, TK221) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…161 Tb was produced via the neutron bombardment of enriched [ 160 Gd][Gd 2 O 3 (98.2%) targets using the high thermal neutron flux (3 × 10 14 neutrons/cm 2 /s) BR2 reactor at SCK-CEN (Belgium) [ 26 ] and subsequently purified at TRIUMF using a semi-automated TRASIS system with solid phase extraction (SPE) resins (TK211, TK 212, TK221) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…161 Tb was produced via the neutron bombardment of enriched [ 160 Gd][Gd 2 O 3 (98.2%) targets using the high thermal neutron flux (3 × 10 14 neutrons/cm 2 /s) BR2 reactor at SCK-CEN (Belgium) [ 26 ]. After cooling, the 161 Tb activity was purified using a semi-automated TRASIS system equipped with TrisKem solid phase extraction (SPE) resins (TK211, TK212, TK221 (Triskem, Bruz, France) at TRIUMF (Canada) as described by McNeil et al [ 27 ]. A radionuclidic purity of > 99% was determined using ICPMS for 161 Tb purified using this approach.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, Aziz and Artha reported the quantitative separation of terbium-161 from gadolinium targets using extraction chromatography on an LN resin column and sequential elution of gadolinium in 0.8 M HNO 3 solution and terbium in 3 M HNO 3 52 . More recently an automated lab-scale method was developed that relies on small solid-phase extraction using a combination of LN-type extraction resins, making it more compatible with automation using commercially available systems like the Trasis All-in-One system 53 . Using this technique, terbium-161 could be successfully purified from smaller scale targets with high radionuclide and chemical purity.…”
Section: Radionuclide Properties and Production Methods Of The Four C...mentioning
confidence: 99%
“…Using this technique, terbium-161 could be successfully purified from smaller scale targets with high radionuclide and chemical purity. Though the researchers have suggested that there is room for further improvements to minimize the presence of the gadolinium-160 target material and the dysprosium-161 decay product in the final terbium-161 sample, it remains evident that full automation of the purification process holds immense potential when it comes to upscaling production and managing larger quantities of target material 53 . These small modular systems could be interesting for final refinement of terbium-161 after bulk separation on a different location or system, or could be used for fast reprocessing of terbium-161 after several days of decay to remove the dysprosium-161 daughter reducing its interference during radiolabeling.…”
Section: Radionuclide Properties and Production Methods Of The Four C...mentioning
confidence: 99%
“…It is increasingly accepted that 161 Tb has therapeutic advantages compared to 177 Lu (vide supra), as well as similar production potential. A recent article by McNeil recognizes a confounding limitation of 161 Tb production, which has been spearheaded by groups at the Paul Scherrer Institute in Switzerland for the past several years, namely, that the highest quality productions of 161 Tb reported so far are constrained by the availability of uniquely small meshed ion exchange resin materials (McNeil et al 2022). While other high performance ion chromatography-(HPIC-) based separation methods are being developed elsewhere, high-pressure processes present particular challenges to scale-up and are substantially more challenging to implement than the cartridge-based method reported here using materials that are readily commercially available at reasonable cost.…”
Section: By Jonathan Englementioning
confidence: 99%